State Incentives of Investment Activity in fuel and Power-Engineering Complex in the Russian Federation - A. V. Bystrov; Е. А. Talatin (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
The article grounds the necessity to take into account the market specificity of state incentives of investment activity. It describes factors of fuel and power-engineering complex transformation in the Russian Federation in conditions of power globalization and the World Trade Organization extension. The fact that there are a lot of problems in the fuel and power-engineering complex of the Russian Federation envisages topicality of state incentives of investment activity in the field of power project implementation. The author identifies factor variables of specific features of the fuel and power-engineering complex on the national level and underlines the need to put into life the comprehensive investment steps in the field of fuel and power-engineering complex of the Russian Federation.  The article provides characteristics of overseas tools of state incentives of investment activity in the fuel and powerengineering complex viewed from specificity of their use. Warranties and finance support on the part of state in stimulating investment activity in the fuel and power - engineering complex are studied. Key integral elements of the system of state regulation in investment activity in the fuel and power-engineering complex are shown in the article, as well as indications of effective state incentives in the fuel and power-engineering complex. Finally, the author comes to the conclusion that state incentives of investment activity needs transformation in view of methodology.